Kepastian Hukum Dalam Rangka Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil Melalui One Map Policy - Zulharman (Universitas Teknologi Surabaya, 2023)
Abstract. For legal guarantees and legal certainty, the principles of justice, feasibility and propriety must be put forward and technically contributed to the accuracy of mapping to resolve the complexity of problems related to natural resources, in this case coastal areas and small islands and considering the chaotic regional problems, the president and the government to overcome this created a One Map Policy with a Map Accuracy Level of 1:50,000 Scale. This article tries to analyze how this one map policy is an instrument in ensuring legal certainty in the management of coastal areas and small islands. This type of research is normative juridical research. This legal research is carried out by examining library materials or secondary data alone. Secondary materials to be researched include statutory regulations and various judge's decisions that are relevant to this research. Normative legal research in this research will also include: Research on legal principles; research on legal synchronization; as well as legal history research. This research uses a statutory approach and a conceptual approach. In this article, it was found that there are still several problems in this case related to spatial planning which are still overlapping and sectoral in nature and policies related to detailed maps.